Extended Release Combination Antibiotic Therapy from a Bone Void Filling Putty for Treatment of Osteomyelitis - Hasan, Raquib (Pharmaceutics, 2019)
In spite of advances in Total Joint Replacements (TJR), infection remains a major concern and a primary causative factor for revision surgery. Current clinical standards treat these osteomyelitis infections with antibiotic-laden poly(methyl methacrylate) (PMMA)-based cement, which has several disadvantages, including inadequate local drug release kinetics, antibiotic leaching for a prolonged period and additional surgical interventions to remove it, etc. Moreover, not all antibiotics (e.g., rifampicin, a potent antibiofilm antibiotic) are compatible with PMMA. For this reason, treatment of TJR-associated infections and related complications remains a significant concern. The objective of this study was to develop a polymer-controlled dual antibiotic-releasing bone void filler (ABVF) with an underlying osseointegrating substrate to treat TJR implant-associated biofilm infections. An ABVF putty was designed to provide sustained vancomycin and rifampicin antibiotic release for 6 weeks while concurrently providing an osseointegrating support for regrowth of lost bone. The reported ABVF showed efficient antibacterial and antibiofilm activity both in vitro and in a rat infection model where the ABVF both showed complete bacterial elimination and supported bone growth. Furthermore, in an in vivo k-wire-based biofilm infection model, the ABVF putty was also able to eliminate the biofilm infection while supporting osseointegration. The retrieved k-wire implants were also free from biofilm and bacterial burden. The ABVF putty delivering combination antibiotics demonstrated that it can be a viable treatment option for implant-related osteomyelitis and may lead to retention of the hardware while enabling single-stage surgery.